Evaluation of the Commonwealth Secretariat's strategy for gender equality and gender mainstreaming - Daniel, Patricia...[et al.] (Commonwealth Secretariat. Strategic Planning and Evaluation Division LondonGB, 2007)
Concludes the Performance Audit of the Commonwealth Secretariat Strategy for Gender Equality and Gender Mainstreaming carried out between January 2006 and January 2007. Summarizes and discusses the key findings from all stages of the audit and makes recommendations for future deliberations within the organisation.